Terapi Bekam Basah Terhadap Penurunan Kadar Asam Urat Dalam Darah - Arif Tirtana; Muhammad Habib (Journal of Health (JoH), 2023)
Uncontrolled uric acid in the blood can lead to hyperuricemia. Symptoms that arise are pain, swollen, inflamed, hot and stiff joints so that the sufferer cannot carry out activities as usual. The morbidity rate of patients at 34 years is 32% and aged over 34 years is 68%. To suppress the symptoms of hyperuricemia, treatment can be done by removing static blood containing toxins from the human body. Research Objectives To determine the effect of wet cupping (al-hijamah) on reducing uric acid levels in the blood. The method in this research is using the PICOS framework, Population/ Problem (P), Intervention (I), Comparison (C), Results (O), Study Design (S). The initial stage of selecting articles with the keywords "uric acid" and "cupping" was found in 1627 journals. A total of 312 data did not match the title, and as many as 32 data did not match the problem formulation and objectives. So that obtained 8 journals in accordance with the inclusion criteria of the study. Search literature through Google Scholar database, Springer Link, Science direct. The results of a journal study, wet cupping can reduce uric acid levels in the blood with a significant value (P<0.05).